Pediatric congenital hydronephrosis (ureteropelvic junction obstruction): Medical management guide. (11th March 2020) - Kohno, Miyuki; Ogawa, Tetsushi; Kojima, Yoshiyuki; Sakoda, Akiko; Johnin, Kazuyoshi; Sugita, Yoshifumi; Nakane, Akihiro; Noguchi, Mitsuru; Moriya, Kimihiko; Hattori, Motoshi; Hayashi, Yutaro; Kubota, Masayuki
Abstract: The prevalence of asymptomatic hydronephrosis, now detected by ultrasonography, has increased. However, definitive management guidelines for the management of congenital hydronephrosis have not been established. The Japanese Society of Pediatric Urology created a "medical management guide" based on new findings for physicians practicing pediatric urology. We developed a medical management guide focused on congenital hydronephrosis caused by ureteropelvic junction obstruction. This medical management guide consists of the definition, pathophysiology, epidemiology, diagnosis, classification, treatment using a clinical management algorithm of hydronephrosis and the long‐term course of the disease. The aim of hydronephrosis management is to determine whether surgery should be carried out to avoid renal dysfunction, as there is a possibility for improvement without intervention. Ultrasonography is essential to make treatment decisions. Management is determined by a comprehensive assessment, including the degree of hydronephrosis, anterior–posterior diameter of the renal pelvis and, if necessary, a nuclear medicine evaluation of the status of urine drainage and renal function.